Tingkat pengetahuan dan sikap ibu terkait makanan tambahan dengan status gizi balita di Kecamatan Woyla Barat - Maharani Maharani; Sri Wahyuni; Diah Fitrianti (Jurusan Gizi Politeknik Kesehatan Kemenkes Aceh, 2019)
The double burden of nutrition is very worrying for children in Indonesia. Indonesia has a prevalence of malnutrition of 13,8% and 3,1% was overweight of children, while in Aceh that is 16,8% and 2,9% of overweight. One of the factors is the arrangement of additional food that is not patterned. The purpose of this study was to examine the relationship between mother's knowledge and attitudes about supplementary food and nutritional status in infants. The study was an analytic survey using a cross sectional approach. Samples were taken as many as 86 toddlers with a simple random technique. Data collection using questionnaires and anthropometric measurements. Knowledge and attitude data are processed according to percentage values, and nutritional status data are processed according index to WFA. The statistical test is chi-square at CI:95%. The results showed that mothers' knowledge and attitudes about supplementary food were still not good, and there were still many toddlers with the best nutritional status. Other results show the relationship between maternal knowledge (p=0,000) and maternal attitudes (p=0,019) regarding supplementary food with nutritional status in toddlers in Woyla Barat District. Conclusions, poor mother's knowledge and attitude about supplementary feeding is related to the high problem of malnutrition and over nutrition. Suggestions, counseling is needed related to providing good and nutritious supplementary food, as well as monitoring the nutritional status of children continuously both in the WFA, HFA and WFH indexs.Beban ganda masalah gizi sangat mengkhawatirkan anak-anak di Indonesia. Indonesia mempunyai prevalensi kekurangan gizi sebesar 13,8% dan 3,1% balita gizi lebih, sedangkan di Aceh yaitu sebesar 16,8% dan 2,9% anak gizi lebih. Salah satu faktor penyebab yaitu pengaturan makanan tambahan yang tidak terpola. Tujuan penelitian untuk mengukut hubungan pengetahuan dan sikap ibu tentang makanan tambahan dengan status gizi pada balita di. Penelitian bersifat survey analitik dengan menggunakan pendekatan cross sectional. Sampel diambil sebanyak 86 balita dengan teknik acak sederhana. Pengumpulan data menggunakan kuesioner dan pengukuran antropometri. Data pengetahuan dan sikap diolah menurut nilai persetase, dan data status gizi diolah menurut indeks BB/U. Uji statistik yaitu chi-square pada CI:95%. Hasil penelitian menunjukan pengetahuan dan sikap ibu tentang makanan tambahan masih kurang baik, serta masih banyak balita yang bestatus gizi kurang. Hasil lainnya menunjukkan hubungan antara pengetahuan ibu (p= 0,000) dan sikap ibu (p= 0,019) tentang makanan tambahan dengan status gizi pada balita di Kecamatan Woyla Barat Kabupaten. Kesimpulan, pengetahuan dan sikap ibu yang kurang baik tentang pemberian makannan tambahan berhubungan dengan tingginya masalah gizi kurang dan kelebihan gizi. Saran, perlu dilakukan penyuluhan terkait pemberian makanan tambahan yang baik dan bergizi, serta pemantauan status gizi anak secara terus menerus baik pada indeks BB/U, TB/U dan BB/TB.